Hubungan Bermain Game Online dengan Kejadian Insomnia pada Siswa Kelas XI SMA Mahardhika Surabaya - Sri Wilujeng; Roufuddin Roufuddin; Sosilo Yobel; Christa Welli Goo (STIKES Adi Husada, 2025)
Many teenagers were trapped playing online games late into the night, which can lead to insomnia. Insomnia could impact mental and physical health, reducing concentration and affecting mood. Therefore, parents needed to limit online gaming time and provide healthier and more positive entertainment activities for teenagers. The purpose of this study was to determine the relationship between playing online games and the incidence of insomnia. This research method used a correlation analytic design with a cross-sectional approach. The number of samples in this study was 37 students using a total sampling technique. The instrument used a questionnaire. The validity test of the questionnaire in this study used the Spearman Rank test. The results showed that most of the eleventh grade students of SMA Mahardhika Surabaya (62.2%), namely 23 students rarely played online games and most (62.2%), namely 23 students experienced mild insomnia. The results of the study showed P = 0.092. with Î± = 0.05, namely P more than Î±. This means that there were no relationship between playing online games and the incidence of insomnia in class XI students of SMA Mahardhika Surabaya. The strength of the relationship was sufficient with a correlation coefficient value = 0.28 and was in the same direction, the lower the frequency of playing online games, the lower the incidence of insomnia. Thus, students were expected to reduce the time playing online games and did other more useful activities.